Male courtship reduces the risk of female aggression in web-building spiders but varies in structure. (12th December 2021) - Wignall, Anne E; Herberstein, Marie E
Abstract: Male courtship serves multiple functions in addition to inducing females to accept them as a mate. In predatory species, male courtship can function to reduce the risk of sexual cannibalism. This is particularly important in web-building spiders in which males risk being mistaken for prey when they enter the female's predatory trap—the web—in order to commence courtship. Male spiders generate vibrations by shuddering in the female's web. Shudder vibrations can delay female aggression, even toward prey struggling in the web. We predicted that shudder vibrations are highly conserved across species of web-building spider as males all face the same constraint of not being mistaken for prey by females. We examined how conserved shudder vibrations are across web-building spiders by testing whether female Trichonephila plumipes delay aggressive behavior toward real prey struggling in the web during playback of conspecific or heterospecific ( Argiope keyserlingi ) male shudder vibrations. We found that while conspecific shudder vibrations do indeed delay female predatory behavior, heterospecific male shudder vibrations do not. There is evidence of shudder or shudder-like vibrations in male courtship behavior across web-building spider families, but these vary in structure. This suggests that despite strong constraints on courtship signal design to separate predatory responses from sexual responses, there is additional selection driving the divergence of signals across distantly related spider species. Abstract : Male spiders risk being mistaken for prey during courtship. To reduce this risk, males "shudder" in webs to reduce female aggression. Shudder vibrations even delay female aggression toward real prey in her web. The structure of shudder vibrations do not overlap with prey vibrations. However, distantly related spiders use different shudder signals, indicating that female preferences also drive species specific courtship vibrations.